Assessing the Susceptibility Status of Mosquitoes (Diptera: Culicidae) in a Dirofilariasis Focus, Northwestern Iran - Abolfazl Ataie; SeyedHassan Moosa-Kazemi; Hassan Vatandoost; MohammadReza Yaghoobi- Ershadi; Hasan Bakhshi; Mehdi Anjomruz (Tehran University of Medical Sciences, 2015)
Background: Mosquitoes are considered as the vectors of dirofilariasis and some vector borne disease in Iran. The objective of this study was to determine the susceptibility level of the vectors to various insecticides recommended by WHO for any control measures in an endemic area in northwestern Iran. Methods: Mosquito larval and adult collections were carried out using different methods provided by WHO including dipping and hand catch techniques. The susceptibility level was assessed to DDT 4%, malathion 5%, propoxur 0.1%, deltamethrin 0.05% and lambda-cyhalothrin 0.05%. Results: Totally, 749 adults and 5060 larvae of Culicidae mosquitoes were collected comprising seven species of adult and larvae, including: Anopheles claviger, An. maculipennis, An. sacharovi, Culex hortensis, Cx. pipiens, Cx. theileri and Culiseta longiaerolata. Frequency of larvae and adults of An. maculipennis was very low, so susceptibility tests on this species did not performed. Results showed that Cx. theileri, Cs. longiaerolata and Cx. pipiens were resistant to DDT 4%, lambda-cyhalothrin 0.05%, and propoxur 0.1% whereas found tolerant to deltamethrin 0.05% and malathion 5%. The LT50 and LT90 values for five insecticides were calculated. Conclusion: We suggest the same study in different parts of the world to obtain the data due to bionomic and susceptibility status of dirofilariasis vectors. This information will help the health authorities for monitoring and evaluation of control measures.